Ion temperature gradient mode linear and nonlinear structures in electron-ion plasma,with stationary charged dust grain: DOI : 10.48129/kjs.18847 - Khan, Aziz Khan; U. Zakir; A. Rahman; J. Ali; Q. Haque (Kuwait Journal of Science, 2023)
Ion temperature gradient mode nonlinear structures are studied with stationary charged dust. The dynam-ical role here is played by heavy ions. The small amplitude limit infuence of various plasma parameters shows that the phase velocity of the mode modifes the overall plasma dynamics. Further, from the solu-tion of the model equations we obtain Kortweg-de-Vries (KdV) and Korteweg-de-Vries Burger (KdVB) like equations, the solution of which gives solitary and shock wave nonlinear structures. Numerical anal-ysis of these nonlinear structures shows that dust number density and polarity have a substantial impact on these structures. The present observation may be benefcial in space and laboratory plasma investiga-tions.